Efficacy of ethyl ascorbyl ether–containing cosmetic cream on blue light–induced skin changes. (29th May 2021) - Jo, Hong Li; Jung, Yuchul; Kim, Young Kyun; Kim, Nahee; Cho, Eunbyul; Han, Jiyeon; Hwang, Yoon Kyun; Suh, Byung‐Fhy; Kim, Eunjoo
Abstract: Background: Office workers are consistently exposed to blue light, mainly from sunlight and digital device. Recent studies report that blue light has various harmful effects, including cellular changes via reactive oxygen species. Studies on blue light–induced skin changes have only been conducted in vitro and have not been clinically confirmed. Objective: We provide novel methods to evaluate the effect of the product on the recovery of skin changed by blue light. Methods: Internet surveys were conducted for workers in their 20s and 40s regarding exposure time to blue light in various environments. To study the effects of long‐term exposure to blue light (456 nm) on the skin, we designed three light intensity conditions, and various skin characteristics were observed. After blue light irradiation, various skin characteristics were analyzed before and after applying ethyl ascorbyl ether (EAE)–containing cosmetic cream for 2 weeks. Results: When exposed to strong blue light for approximately 16 days, the L * value, skin hydration, transparency, and elasticity decreased, and the melanin index, erythema index, a * value, and b * value increased. Furthermore, after short‐term blue light irradiation (dose, 269 J/cm 2, the equivalent of blue light exposure for approximately 38 days in daily life), the L * value and elasticity decreased, and the melanin index and erythema index increased. However, when EAE cream was applied on skin for 1–2 weeks, the skin recovered. Conclusion: This study clinically confirms the skin changes caused by blue light and the effect of EAE in relieving such changes.